CLASSİFİCATİONS ANALYSİNG CULTURE (Third Sector Social Economic Review, 2020)
It’s seen that most of cultural emprical studies in national literature are written towards a few culture cassifications (studies). From these studies the ones which are shaped on dimensions generally have used Hofstede’s culture classification and the ones shaped on values are generally have used Rokeach’s or Schwartz’s culture study. This shows that in national literature the studies such as GLOBE research which has found different up date results about Turkey and other cultural studies shaped on dimensions are ignored in where some basic culture studies shaped on values are disregarded. The aim of this study is to explain basic cultural classifications by including the ones which are used in literature but rarely used in national literature. In this theoretical study cultural classifications are examined relatedly with each other in integrity. In the study these cultural classifications are handled in integrity by a detailed literature review and it’s hoped to offer a theoretical background for the researchers whom want to study culture concept in the future in national literature.
Keywords: Culture; Dimensions; Values